Breedbot: an evolutionary application in digital content. - Miglino O; Gigliotta O; Ponticorvo M; Nolfi S (Electronic Library, 2008)
Purpose-This paper aims to describe an integrated hardware/software system based on evolutionary robotics and its application in an edutainment context.Design/methodology/approach-The system is based on a wide variety of artificial life techniques (artificial neural networks, genetic algorithms, user-guided evolutionary design and evolutionary robotics). A user without any computer programming skill can determine the robot's behavior in two different ways: artificial breeding or artificial evolution. Breedbot has been used as a didactic tool in teaching evolutionary biology and as a 'futuristic' toy by several science centers. The digital side of Breedbot can be downloaded on the web site: www.isl.unina.it/breedbotFindings-The results in this pilot study suggest that using Breedbot in an educational context can be useful to improve learning in biology.Research limitations/implications-As this is a pilot study, one limitation is the small sample considered. The issue will be investigated further with a wider population and subject-matter, which will also improve the Breedbot system.Practical implications-These results suggest that tools like Breedbot could be introduced into biology curricula at schools.Originality/value-The paper describes an original application in digital content and shows the importance of using such a tool in an Edutainment context. It is therefore interesting for teachers, vocational trainers and anyone involved in educational activities.